Optimizing methylene blue dye adsorption onto liquid natural rubber-based hydrogel: kinetics, isotherms and reusability - Abdul Sattar, Omar D.; Rozida Mohd Khalid,; Siti Fairus M. Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, notable advancements have taken place in the textile industry, particularly with the widespread use of synthetic dyes such as methylene blue (MB). However, the environmental impact of these dyes has raised significant concerns. Their potential to influence both chemical and biochemical demand poses risks, leading to potential disruptions in aquatic plant photosynthesis. Additionally, concerns exist regarding the toxicity and potential carcinogenicity of these dyes to humans. This study achieved successful hydrogel synthesis through the efficient utilization of ultrasonic methods, combining liquid natural rubber (LNR), acrylic acid (AAc), and pectin (Pc) to adsorb MB from aqueous solutions. Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) were employed to analyze the structure. Utilizing Response Surface Methodology (RSM), the study investigated the effects of the AAc:LNR weight ratio and Pc weight on hydrogel preparation for MB removal. This led to the development of a quadratic polynomial model with an ANOVA-derived R2 value of 0.9970. Optimal conditions for hydrogel production were identified as a 3.00 g/g AAc:LNR weight ratio and 0.0325g of Pc, resulting in an impressive 99.07% MB removal effectiveness. The limit of detection (LOD) for methylene blue adsorption was calculated at 0.64 ppm. The kinetics and isotherms of MB removal were described by the pseudo-second-order and Freundlich models, respectively. Furthermore, the investigation into hydrogel reusability demonstrated its capability for up to five utilization cycles. The LNR/AAc/Pc hydrogel exhibits promising potential as an effective, cost-efficient, and environmentally conscious adsorbent for MB removal. This makes it applicable to water treatment scenarios involving cationic dyes.